Investigating How Newly Appointed CEO’s Enact Corporate Turnaround in the Aerospace & Defence Industry - Cox, Duncan (2009)
Increased literary attention and debate has been directed at business turnaround in recent years; albeit as Furman & McGahan (2002, p.238) suggest; ‘despite their centrality, little is still known about their prevalence or trajectory’. This case study departs from most other turnaround research by addressing the global Aerospace and Defence sector; of which has remained unexplored until this point. Specifically, it looks to ascertain ‘how new top management enact successful turnaround’ and consequently, ‘what characteristics inform these actions?’ Using a cross-case analysis, the studied firms of BAE Systems, Boeing and VT Group were observed to predominantly deploy resources toward strategic orientations, hence comprising the basis for achieving successful turnaround. Furthermore, executives’ human capital- exemplified within their generic skills combined with long and short term approaches; were found significant in informing choices of strategic orientations which precipitated successful turnaround. It is acknowledged that the study’s was limitations were derived from its small sample size and moreover, the cyclical complexity of the industry. However, this is tempered by the fact that emphasis on growth industries, application of the RBV and the merging of turnaround research with top management characteristics; provides a basis from which hopefully, more robust and conclusive research is stimulated.